(untitled) (Al-Academy, 2015)
The (Richard Wagner) of cultural figures rare collected between philosophy and literature and the arts to reach the concept of the artwork destruction (Gesamtkunstwerk), who called for by the movement romantic, he is a thinker, and composer renewed, and playwright, designer and architect of a special kind.Able ( Wagner ) that translates his thoughts technical and design in the field of opera and disclose those ideas models actual dealt joints essential this art heritage, which was developed and laid his modern rules approach by achieving his dream creates theater ideal, which was held in the city ( Bayreuth) in ( Bavaria ), one of the German Federal States .The study reviews the ideas of Wagner and their sources, which have had an important role in the development of his artistic and personal reflections on his production artwork and aspirations of the philosophical, which achieved through which its own concept, which combines the between (the dictatorship of the artist and democracy) to get safely to the treatment of social optimization and ensure results.Address the study is to identify the character (Wagner) in all aspects of cultural, artistic and political, as it is each of them an important tributary of the shares in the establishment of his theory of art opera that corrected the track (from his point of view) and head it towards the interaction with the requirements of life renewed in order to live art with the community and meet cultural needs and aspirations of the modern man.Finally, the study found effects (Wagner) in subsequent generations whether it be the elite avant-garde filmmakers of the modern theater builders, or in writing orchestral and operatic, or in foundations adopted by the opera houses and modern architecture.Keywords: Wagner, theater, opera, Gesamtkunstwerk.